(untitled) (Research, Society and Development, 2023)
Proposing pedagogical procedures that awaken and build meaningful learning in the school environment, in particular, in the classroom, is an issue that has motivated researchers to bring knowledge of how the day-to-day life of the class with Deaf students in regular education is happening and how teaching can be more accessible with the student’s learning reality. The article aims to show the pedagogical practices of teachers in the early years of elementary school used with deaf students at a municipal school in Tutóia-MA. The research was a report of experiences in a 3rd year class, in the afternoon, in a descriptive, qualitative way, observations and the construction of a logbook. With the data found, the teacher at first presented many difficulties, having to seek help from Libras teachers working at the municipal education department. However, this was oriented to take a course on how to use visual materials and real resources, such as fitting games, images, scrap material (caps, toothpicks, seeds) and drawings made on the whiteboard of the proposed subjects, and other materials. It can be said that, with the acquisition of didactic resources for the classroom by the teacher, the student began to develop skills in reading, writing, calculations and other necessary skills for his personal and social autonomy.